The Effectiveness of CORE (Connecting, Organizing, Reflecting, and Extending) Learning Model on Students’ Learning Outcomes in Islamic Religious Education - Nabila, Aisyah Hilwa; Jamaluddin, Wan; Hasanah, Uswatun (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This research investigates the effectiveness of the CORE learning model—Connecting, Organizing, Reflecting, and Extending—in enhancing students’ learning outcomes in Islamic Religious Education (IRE) at SMP Negeri 36 Bandar Lampung. The study was conducted in response to students’ relatively low performance in higher-order thinking skills, indicating the necessity for instructional approaches that are more contextual, interactive, and student-centered. A quantitative approach was applied using a quasi-experimental design with a post-test-only control group. The participants consisted of two eighth-grade classes selected through simple random sampling, in which the experimental group was taught using the CORE learning model, while the control group received instruction through conventional teaching methods. Data were collected using a multiple-choice achievement test that had been confirmed to be valid and reliable, with a reliability coefficient of α = 0.834. The results reveal that the CORE learning model significantly improves students’ learning outcomes, particularly in higher-order cognitive domains (C4–C6). The application of the CORE model promotes active participation, collaboration, and reflective learning, thereby enabling students to develop a deeper and more meaningful understanding of Islamic Religious Education concepts. Overall, this study offers both theoretical and practical contributions to the advancement of innovative, twenty-first-century-oriented teaching strategies in Islamic Religious Education.